EVALUASI KINERJA DAN PENGEMBANGAN TERMINAL PENUMPANG GAMALAMA KOTA TERNATE MALUKU UTARA - , MUHAMMAD RIZAL, Ir. Djoko Murwono, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Passenger station is part of the transport system network which is needed by public means of transportation that it has dominant role and function in the system. Station Gamalama in Ternate is consideret as passenger station type C. This type of station needs special consideration, especially in its development planning, due to its function as connector between urban and rural transportation. This research analyzes the circulation of public transport facilities, the average headway of public transportâs departure and arrival, the facility of passenger and visitor, the traffic around the station, as well as the development of the station itself. The result of the analysis shows that the VC ratio of road networkâs performance around station Gamalama is 0.517. Type of public transport in ternate is Suzuki Carry of which capacity is 8 passenger and its load factor 0.69. The average headway of public transport which arriver and departs from Station Gamalama is 27.3 second and 28,5 second. The average idle time of public transport inside the station is 15.53 minutes per day. On the peak hours, the average number of public transports to enter the station is 56 per 15 minutes. The development of Station Gamalama is suggested in relation with its function as Station type C. Based on the analysis, the total area needed for the development of the station is 8.811 m2.